MENGEKSPLORASI PENDEKATAN STEM DALAM PENGEMBANGAN BAHAN AJAR MATEMATIKA TERHADAP KEMAMPUAN MATEMATIS: SYSTEMATIC LITERATURE REVIEW - Nuraini, Clarisa (UNIVERSITAS TANJUNGPURA, 2024)
In today's world of education, various approaches can be used as part of contextual learning. Various types of approaches can be applied in learning, one of which is based on Science, Technology, Engineering and Mathematics (STEM). The STEM approach by developing learning teaching materials aims to improve mathematical abilities at various levels of education. The purpose of this study was to determine the effectiveness of STEM-based teaching materials in mathematics learning and the success of STEM-based mathematics teaching materials on mathematical abilities. There are 10 articles that have been selected according to the inclusion criteria will be analyzed using the SLR (Systematic Literature Review) method. The research results obtained in the form of mathematics teaching materials using the STEM approach have proven their validity, practicality and effectiveness when applied in mathematics learning and also show an increase in mathematical abilities at various levels of education. Further research is needed to explore more deeply so that the implementation of the STEM approach can be optimized when implementing mathematics learning.